Reflections about the environmental teacher's thought: investigative way with a meaning of place - C. A. Chacón (Universidad del Magdalena, 2013)
This article presents some reflections about a doctoral research; it shows how important is to find the conditions of the environmental teacher's thought, as symbolic body and with a meaning of place, that is to say, where he/she spreads out his/her teaching role. Besides, it emphasizes on problemic features that have to do with his/her condition of environmental teacher and on the way as the environmental philosophy takes part in the transformation of his/her thought.